Interpreting the New Testament an introduction to the principles and methods of New Testament exegesis - Conzelmann, Hans; Lindemann, Andreas; Schatzmann, Seigfried S. (Peabody, MA Hendrickson, 1988)
Includes bibliographical references and indexes.
Translated from Arbeitbuch zum Neuen Testament, 8th rev. ed., Tubingen, Germany : J.C.B. Mohr (Paul Siebeck), 1985. First ed. published 1975.
Keywords: Bible. N.T. -- criticism, interpretation, etc. -- methods